2012
DOI: 10.1016/j.cossms.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Advanced synthesis techniques and routes to new single-phase multiferroics

Abstract: Peer reviewed eScholarship.org Powered by the California Digital Library University of California This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
58
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 286 publications
(290 reference statements)
0
58
1
Order By: Relevance
“…Therefore, the SrRuO 3 /SrTiO 3 system has strong interfacial bonds, a commensurate chemical structure and commensurate bonds on both sides of the interface, with a lattice mismatch of only 0.6% at room temperature. [16][17][18] Transmission electron microscopy studies demonstrate that pulsed laser deposited SrRuO 3 thin-films can possess coherent and chemically abrupt interfaces with an underlying oxide substrate. 19,20 In short, the SrRuO 3 /SrTiO 3 system possesses a model interface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the SrRuO 3 /SrTiO 3 system has strong interfacial bonds, a commensurate chemical structure and commensurate bonds on both sides of the interface, with a lattice mismatch of only 0.6% at room temperature. [16][17][18] Transmission electron microscopy studies demonstrate that pulsed laser deposited SrRuO 3 thin-films can possess coherent and chemically abrupt interfaces with an underlying oxide substrate. 19,20 In short, the SrRuO 3 /SrTiO 3 system possesses a model interface.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recent experimental work has demonstrated that the control of film orientation is one promising and effective approach to manipulate ferroelectric domain structure and properties. 3,4 In studies of thin-film materials, such as the model ferroelectrics PbZr 1−x Ti x O 3 and BiFeO 3 , it has been noted that the variation of film orientation could result in exotic crystal and domain structures and give rise to enhanced ferroelectric susceptibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Exchange enhancement, common to both types of BiFeO3 films, likely arises from a coupling of the ferromagnetic moments of the Co0.9Fe0.1 to the small canted moments due to the Dzyaloshinski- 14 Moriya interaction (~ 0.02 ÎŒB/Fe) in the bulk of the BiFeO3 domain surface. 47 Exchange bias, on the other hand, requires the presence of pinned, uncompensated spins in the antiferromagnet.…”
mentioning
confidence: 99%
“…14 In the bulk, BiFeO3 has a rhombohedral structure and the polarization is oriented along < 111 > (note that pseudocubic indices are used throughout, unless otherwise specified), leading to three types of possible domain walls separating regions with polarization orientations 4 differing by 71°, 109°, and 180°. Charge neutrality and mechanical compatibility conditions impose constraints on the orientations of these domain walls: equilibrium uncharged 71° and 109° domain walls occur on {101} and {100}, respectively; while uncharged 180° domain walls form in crystallographic planes parallel to the polarization vectors inside the adjacent domains.…”
mentioning
confidence: 99%